Non-Executive Employee Ownership and Corporate Risk - Bova, Francesco; Kolev, Kalin; Thomas, Jacob K.; Zhang, X. Frank (The Accounting Review, 2015)
ABSTRACT Prior research documents a negative link between risk and executive holding of stock, but a corresponding positive link for options. We find a similar negative relation for non-executive holding of stock. Our finding is consistent with the view that non-executives not only face significant incentives to reduce risk when they hold stock, but they are also able to affect corporate risk. While endogeneity cannot be ruled out fully, the results of a battery of tests suggest that it plays a limited role. A second robust result is that the documented relation becomes more negative as option-based executive compensation increases. Overall, corporate risk is related to the incentives created by stock and options held by both executives and non-executives, as well as interactions among those incentives. JEL Classifications: G30.